Exploring the influence of distant learning and MOOCs in foreign language lecturers’ professional development - khasawneh, Mohmmad (Research Journal in Advanced Humanities, 2024)
Distance education gradually establishes itself as a part and parcel of the global educational system. Although a great deal of research has been done to address the strategic influence of distance learning and MOOCs on student performance, very little is strategically recognized about digital distance teaching about lecturers’ professional development (PD). This paper conducted a critical qualitative analysis to provide analyses of the perception of FL lecturers regarding how DL and MOOCs affected their PD as well as student performance. Data was collected by carrying out semi-structured interviews, which were underpinned in the TAM model from five lecturers randomly selected and identified as PLT1, PLT2, PLT3, PLT4, and PLT5, respectively, who appeared to have a deeper understanding of the distancing learning phenomenon on their professional development and academic achievement. Thematic analysis was used to account for the collected data, as various themes were looked for in interview transcripts and subsequently formed a basis of study findings and discussion. Across the varied interview transcripts, six main themes were significant, including the theme of impacts teaching toolkits, global collaborations, flexibility and autonomy, exposure to innovative technologies, continuous PD for lecturers, and enriched cross-cultural perspectives. A more significant percentage of the participants also affirmed how useful and easy to participate in distance learning programs and MOOCs are, in connection to their PD. This research provides further evidence that lecturers’ participation in online professional development has a favourable effect on their students’ academic success when it comes to foreign language classes. Therefore, it is concluded that for language teachers to stay abreast of ongoing transformations in the field and prepare appropriate practices, considering learners from different backgrounds as part of the global community, a creative professional development practice reflects their responsibility. Distant learning and MOOCs offer this opportunity with flexible and accessible systems.